Toward a typology of incubators based on HRM - Chaffik Bakkali; Karim Messeghem; Sylvie Sammut (Journal of Innovation and Entrepreneurship, 2014)
The fact that there are major differences between one incubator and another has resulted in many authors working on multiple typologies. Although these typologies are relatively common in the literature, they all tend to use the same classification criteria (objectives of the structures, funding, etc.). In this article, we hope to broaden the viewpoint to human resource management (HRM) within incubators. We defend the theory that the differences between incubators are not only found at the level of their objectives or their funding, but also at the level of their HRM policies. Through conceptual reflection, we thus propose HR management that is specific to each type of structure, based on Pichault and Nizet's configurational approach (2000), as well as on Mahé de Boislandelle's social mix (1993).
Keywords: 650; Business incubators; Typology; HRM